Вольт-фарадные измерения в тонкопленочных эпитаксиальных структурах GaAs - Gorev, N. B.; Kodzhespirova, I. F.; Privalov, E. N. (PE "Politekhperiodika", Book and Journal Publishers, 2009)
It is shown that capacitance–voltage characteristics that feature steeply dropping regions, in particular those of GaAs thin-film structures, may be measured at moderately small amplitudes of the measuring АС voltage (of the order of 100 mV) at the expense of taking measurements at two different amplitudes. This conclusion is confirmed by the results of numerical calculation of the apparent capacitance of GaAs epitaxial structures.